PENGUATAN PENDIDIKAN KARAKTER MELALUI PENERAPAN BUDAYA POSITIF SEKOLAH DI MI NURUL ILMI KOTA BIMA - Eva Kurniati; Syahru Ramadhan; Abdussahid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The decline in the character values of students has become a crucial issue in the field of education today. MI Nurul Ilmi in the city of Bima responds to this condition by implementing a positive school culture as an effort to shape students' character with noble morals. This study aims to describe the process and impact of implementing positive school culture in strengthening character education for students at MI Nurul Ilmi in Bima City. This research uses a qualitative approach with a descriptive type of research. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of the school principal, teachers, and students. Data analysis was performed through stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the positive school culture at MI Nurul Ilmi is implemented through five habituations, namely: Activities in Accordance with the Values of the Pancasila Student Profile, Implementation of Positive and Restorative Discipline, Appreciative Cultural Activities and Positive Reinforcement, Collaboration Activities with Parents and the Community, and Practices of Physical and Social Environments that Support. The implementation of positive school culture at MI Nurul Ilmi in Bima City has shown significant effectiveness in shaping students' character.